The Effect of Vertical Kick Training on 15 Meter Underwater Speed in Swimming Athletes - Anis Asaddun; Bhayu Billiandri (STKIP Pasundan, 2026)
This study aimed to determine the effectiveness of vertical kick training on 15-meter underwater speed in swimming athletes of Tegal Regency. This research used an experimental method with a one group pretest posttest design. The sample consisted of swimming athletes from Tegal Regency who participated in a vertical kick training program for 12 training sessions. Data analysis was carried out using the Shapiro–Wilk normality test, followed by the paired sample t-test to determine the effect of the training program. The statistical analysis was conducted using IBM SPSS Statistics version 32.0. Based on the data analysis, the average pre-test time was 10.4600 seconds, while the average post-test time was 9.9020 seconds. The findings indicated a decrease in time of 0.55800 seconds after the treatment was given. The results showed an improvement in the athletes 15-meter underwater speed after participating in the training program.